A98 SURVEILLANCE COLONOSCOPIES IN ULCERATIVE COLITIS: DOES IT MAKE A DIFFERENCE?. (15th March 2019) - Hu, A; Narula, N
Abstract: Background: Patients with a background history of ulcerative colitis (UC) and Crohn's disease (CD) have a higher risk of colorectal cancer compared to the general population. However, the benefit of surveillance colonoscopies and the ideal intervals for surveillance have not been established. Aims: This study aims to identify the association between surveillance intervals for patients in Ontario with a diagnosis of UC and the incidence and stage of identified CRC. Methods: This study was approved by the Ontario Institute for Clinical Evaluative Sciences (ICES), which permitted access to data from the Ontario Cancer Registry (OCR) and Ontario Health Insurance Plan Claims (OHIP). This allowed us to retrospectively identify UC patients diagnosed from 1994 onwards with an OHIP billing code 556 and their incidence of CRC with an OHIP billing code 153. In addition, by using the ICES data, access to the Discharge Abstract Database (DAD) and Registered Persons Database (RPDB) further allowed stratification of the patients by comorbidities, age and gender respectively. The primary endpoint was a comparison of CRC stage at the time of CRC diagnosis between patients who did not have screening colonoscopies, average screening interval ≤ 3 years and an average screening interval > 3 years. We defined low risk CRC stage as patients according to the Cancer Care Society (CCS) to have a 5-year survival > 80% compared to high risk CRC as patients with 5-year survival < 80%. According to CCS, CRC stages I, IIa, III and IIIa were classified as low risk and CRC stages IIb, IIc, IIIb, IIIc, IIINOS, IV were high risk. Data was then analyzed by SAS 9.4 statistical software. Chi-square testing was used to compare these incidences. Results: Within the ICES database, a total of 264 UC patients developed CRC and had staging information available. Among these patients, those who had average follow-up colonoscopies at a frequency ≤ 3 years presented with an earlier stage of CRC (58.6% of the time) compared to those with follow-up colonoscopies at a frequency of > 3 years (44% of the time) and those with no follow-up (18.5% of the time) (Mantel-Haenszel chi-square p value <0.001). In addition, when looking at long term follow-up at 15-year, there was a survival benefit shown in those CRC individuals who had average colonoscopies ≤ 3 years (75.12%) compared to follow-up > 3 years (70.1%) and no follow-up (57.8%); the p-value = 0.0042. Conclusions: Those UC patients who underwent colonoscopies on average intervals of ≤ 3 years had their CRC detected at earlier stages compared to those who underwent follow-up colonoscopies at > 3 year intervals or those who did not have follow-up colonoscopies. This supports a surveillance interval for UC of ≤ 3 years. Funding Agencies: None